Video-Duets: Intimacy in/and Inhabited Media - Fornaciari, Christina Gontijo (Revista Eletrônica MAPA D2 - Mapa e Programa de Artes em Dança (e Performance) Digital, 2015)
This article refers to Video-duets, a durational video-performance piece, specifically created for digital platform (internet), conceived within the context of Christina Fornaciari’s PhD research. This writing deals with such work shedding light on the relationship between performance, technology and the narratives of “I”, from the perspective that autobi- ographical art engenders new configurations of politics, emancipating bodies and activating affections into the network and into the city.